2011
DOI: 10.1002/rcm.5005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cyanide‐trapped methylated metabonates formed during reactive drug metabolite screening in vitro

Abstract: Reactive metabolites are estimated to be one of the main reasons behind unexpected drug-induced toxicity, by binding covalently to cell proteins or DNA. Due to their high reactivity and short lifespan, reactive metabolites are analyzed after chemical trapping with nucleophilic agents such as glutathione or cyanide. Recently, unexplained and uncharacterized methylated reaction products were reported in a human liver microsome based reactive metabolite trapping assay utilizing potassium cyanide as a trapping age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
5
17
1
Order By: Relevance
“…A report on cyanide-trapped metabonate formation under reactive metabolite screening incubation conditions was recently published (Rousu and Tolonen, 2011). Consistent with our findings, the authors described structural changes to amine moieties of three drugs (propranolol, amlodipine, and ciprofloxacin), resulting in the addition of a CH 2 group and cyano conjugation, and ascribed these structural changes to metabonate formation.…”
Section: Discussionsupporting
confidence: 90%
“…A report on cyanide-trapped metabonate formation under reactive metabolite screening incubation conditions was recently published (Rousu and Tolonen, 2011). Consistent with our findings, the authors described structural changes to amine moieties of three drugs (propranolol, amlodipine, and ciprofloxacin), resulting in the addition of a CH 2 group and cyano conjugation, and ascribed these structural changes to metabonate formation.…”
Section: Discussionsupporting
confidence: 90%
“…CLZinduced hepatotoxicity was considered to be related to the chemically reactive metabolites during CLZ metabolism (3,4,30,31). Our results demonstrated that GA enhanced CLZinduced hepatotoxicity, accompanied by inhibition of CLZ metabolism indexed as formation of CLZ's two metabolites norCLZ and CLZ Noxide.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, our results demonstrated that this one-carbon addition to the alicyclic secondary amines (I and IX) was NADPH dependent, suggesting the involvement of cytochrome P450 enzyme catalyzed bioactivation. We hypothesized that when using potassium carbonate as the one-carbon source in the liver microsomal incubation, the carbamic acid formation would be the first step of this methylation, Iminium ions from piperazine a-carbon oxidation (pathway 1) have been considered a bioactivation process and those from pathway 2 as experimental artifact resulting from the potential interaction with formaldehyde in the incubation buffer (Gorrod and Sai, 1997;Li et al, 2006;Rousu and Tolonen, 2011;Barbara et al, 2012). However, the biologic and toxicological implications of iminium ions via pathway 2 require further investigation for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In our CN-trapping screening on Ndealkylated alicyclic compounds, significant CN adducts with an additional 14 Da were also observed and confirmed as the addition of a methylene group (unpublished data). It has been suggested that this type of N-methylated CN adduct from the secondary alicyclic amines was an experimental artifact, or "metabonate," from an in vitro microsomal incubation system (Gorrod and Sai, 1997;Li et al, 2006;Rousu and Tolonen, 2011;Barbara et al, 2012). In the case of N-methyl piperazines, there are two possible pathways for the formation of Nmethyl piperazine CN adducts (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation